Indonesia Halal Diplomacy: Strategizing Nation Branding to Win Global Market - Nino Viartasiwi; Geubrina Putri Ramadhani; Innayathul Fitrie (Andalas Journal of International Studies (AJIS), 2024)
Indonesia aspires to be the global champion in the halal industry. The growing domestic halal industry and halal economy lay the groundwork for entering the global halal market. The study examines Indonesian halal diplomacy by observing the halal industry's development and the progress of foreign relations to illuminate Indonesia’s strategies to win the global halal market. The research methods is qualitative with review to relevant reports and observation as the main data collection method. The findings indicate that despite Indonesia’s efforts to win the global halal market, it is still remote from achieving its goal. The study argues that to boost halal diplomacy, Indonesia can capitalize on its nation branding as a modern democracy with the largest Muslim population in the world and the society's halal lifestyle. The study suggests that the consolidation of nation branding, the development of a domestic halal ecosystem, government orchestration, and public participation will develop and sustain halal diplomacy.